Onsite Load Bearing Capacity of Curved-up versus Straigt Beams - Youkhanna, Kanaan (European Scientific Journal, ESJ, 2023)
Straight and curved-up beams are cast as part of the frame models. The models are made as single-span, double-span, and triple-span models. Experimental investigation is conducted to predict load capacity of curved-up beams compared to straight beams. Six models: single-span, double-span and triple-span are presented. Onsite, masonry blocks and bricks, steel pipes and gravel are used to load the beams uniformly. Load is applied gradually until failure mechanism. Enhancement to load capacity is observed in the range between 8.67% to 14.12%. The average enhancement ratio can be taken as 11% due to curved-up effect. Load capacity of interior curved-up beam/span will enhance by 120.3% and 131.3% for both straight and curved-up beams.